(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: To find out the diagnostic accuracy of 75 g glucose challenge test with gold standard 100 g OGTT. Materials and Methods: The present cross-sectional study was carried out among Antenatal women attending the antenatal clinic in the Obs & Gynecology Department of RIMS, Ranchi over a period of one and half years from March 2014 to September 2015. All the cases were evaluated by taking detailed clinical history and performing general, systemic and obstetric examination in order to look for any risk factor for GDM. After taking informed written consent all recruited women were subjected to 75 g oral glucose challenge test. All women were called for 100 gm. OGTT after 3-7 days with unrestricted diet including at least 150gm of carbohydrates daily. Plasma glucose level: Fasting ≥ 95mg/dl, 1sthr ≥ 180mg/dl, 2ndhr ≥ 155mg/dl, 3rdhr ≥ 140mg/dl Presence of two or more abnormal values was considered diagnostic of GDM. Results: As it is obvious from the table maximum number of patients were below 25 years (57%). Most of the patient were primigravida (55%), maximum number of women undergoing screening were in 24-32 week of gestational age which was already planned in the study. Majority of patients were having any of the risk factors for GDM. Of the above risk factor most common was advanced maternal age (43%). Remaining common risk factors were previous history of stillbirth/neonatal death (16%) and recurrent abortion (11.33%), diabetes in first degree relatives (7.3%), history of polyhydramnios (7%), and BMI >25 (5.33%). risk factors of GDM were positive for 75g GCT in 9 (7.9%). Out of them 5 (4.4%) cases were having impaired glucose tolerance and 6 (5.3%) were diagnosed to have GDM. 75 gm GCT has 100% sensitivity and 98.97% specificity and it can be considered as reasonably acceptable as screening as well as diagnostic test for GDM. Conclusion: On the basis of result and analysis of the present study, the overall diagnostic accuracy of 75 g GCT is much greater than other proposed screening methods including 50g GCT. It is therefore concluded that this single step test should replace all other screening test and can also replace two step 100 g OGTT as diagnostic test for GDM.